KAJIAN USAHATANI TANAMAN JAGUNG DI KOTA MULIA KABUPATEN PUNCAK JAYA PROVINSI PAPUA - Sekiman . Wonerengga; Jenny . Baroleh; Oktavianus . Porajouw (AGRI-SOSIOEKONOMI, 2016)
This study aimed to determine cost and farm income of maize farming. The study conducted in March 2015 to May 2015, at Mulia City Puncak Jaya Regency, Papua Province used primary data and secondary data. The method for collected data by interviewing with questionnaires. Primary data obtained from maize farmers,total 68 farmers. secondary data obtained from relevant agencies, Departement of Agriculture and Livestock in Puncak Jaya Regency. The analysis using income analysis. The result showed that the average revenue of maize farming is Rp. 1.943.750.- experises cost Rp. 940. 230, so maize farmer net income ranges between Rp. 1003.5209/planting season. R/C > 1 means maize farming at mulia city profitable.Keywords: Cost, Income, Revenue, Farming, Corn, Mulia City, Papua Province